INTEGRATION OF MIND, BODY, AND SOUL: A CONCEPTUAL GUIDANCE TO A HEALTHY LIFESTYLE - Anuratha Rajasegaram; Rajantheran Muniandy, (INTERNATIONAL JOURNAL OF MODERN TRENDS IN SOCIAL SCIENCES (IJMTSS), 2024)
The current conceptual paper focuses on the integration of the mind body and soul and its relation to well-being from a conceptual perspective. Over the last decade, mental health problems in both developed and developing countries are in an alarming rate. Mental health defines as a productive condition in which internal stability allows the person to utilize their capacity to match society's values via basic cognitive and social skills, feeling expression, empathy, and flexibility. This paper explains an overview of the mind, body and soul framework using Tamil ancient scriptural text through a qualitative methodology of hermeneutics theory interpretation. Finding involves in-depth inquiry and analysis of Thirukkural, its practice and the literature in terms of its context and content for interpretation with regards to mind, body, soul in a holistic manner. Future directions in integrative research are proposed based on the scriptural text of Thirukkural.